Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1161/strokeaha.112.675074
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Validation of Transcranial Doppler Criteria in Assessing Recanalization During Intra-arterial Procedures for Acute Ischemic Stroke An International, Multicenter Study

Abstract: E arly restoration of blood flow is strongly associated with improved functional outcomes and reduced mortality in acute ischemic stroke (AIS) patients treated with intravenous thrombolysis (IVT).1-3 Transcranial Doppler (TCD) is a bedside, noninvasive tool for the real-time monitoring of reperfusion therapies by quantifying residual flow grades at the site of occlusion. [4][5][6][7] The investigators of the Interventional Management of Stroke study have developed a set of ultrasound criteria for the early ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…If velocity improved to normal or elevated values (normal or stenotic signals), complete recanalization was diagnosed. [20][21][22] No change in the abnormal waveforms indicated that no recanalization had occurred.…”
Section: Transcranial Doppler Ultrasound Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…If velocity improved to normal or elevated values (normal or stenotic signals), complete recanalization was diagnosed. [20][21][22] No change in the abnormal waveforms indicated that no recanalization had occurred.…”
Section: Transcranial Doppler Ultrasound Protocolmentioning
confidence: 99%
“…Most of them were women (53.1%). The mean age was 74.08±12.15 years, and the median NIHSS score on admission was 20 [18][19][20][21]. The mean time-to-treatment was 164.74±74.84 minutes.…”
Section: Severe Strokementioning
confidence: 99%
“…2 TCD criteria had been previously validated against CTA and digital subtraction angiography in real time. 13,14 TCD and CTA studies were reviewed and adjudicated locally by investigators. Recanalization was defined as an increase in thrombolysis in brain ischemia by ≥1 grade compared with baseline and an overall thrombolysis in brain ischemia ≥2.…”
Section: Vessel Imaging and Clinical Assessmentsmentioning
confidence: 99%
“…However, it should be noted that a recent multicenter study has established the diagnostic accuracy (>80%) of ultrasound criteria for detection of recanalization during real-time TCD monitoring of intra-arterial reperfusion procedures in consecutive patients with AIS. 15 Second, the retrospective design of the present study as well as the lack of a prespecified sample size estimation require a cautious interpretation of the reported findings. Third, the authors did not include all potential confounders including residual flow at the site of intracranial occlusion, stroke subtype, length of thrombus, and degree of collateral circulation in the final multivariate logistic regression model evaluating the time dependency of tPA-induced recanalization.…”
mentioning
confidence: 88%